IMPLEMENTASI PROGRAM KELUARGA BERENCANA PRIA DI KELURAHAN PETOMPON KECAMATAN GAJAHMUNGKUR KOTA SEMARANG - Hanif Eka Septiana; Aufarul Marom; Herbasuki Nurcahyanto (Journal of Public Policy and Management Review, 2022)
Family Planning Program (KB) is an action that can help individuals as well as husband and wife couples to avoid unwanted pregnancies or births. The target of this Family Planning Program is couples of childbearing age in order to control fertility rates. It is hoped that the implementation of this family planning program is not only carried out by women but also by men, so that there is no gender inequality in the implementation of the program. The purpose of this study was to analyze the implementation and inhibiting factors of the male family planning program policy. This research use desciptive qualitative approach. Data collection techniques through interviews, observation, and documentation. Based on the results of the study, the implementation of the Male family planning program in Petompon village has not gone well because there is no program socialization to the community, there is no increase in users of male family planning acceptors in the Petompon area. The driving factor for the implementation of the male family planning program in the Petompon village is the transportation money given to the community. Inhibiting factors in the implementation of male family planning programs in Petompon sub-district have low resources, culture that influences people's mindsets, economic level that affects the choice of contraception and the attitude of community rejection, especially husbands regarding male family planning programs because people think family planning is a woman's